Assessment of Performance on Community Management of Acute Malnutrition in Wagini OTP Center, Batsari Local Government Area of Katsina State - Bello Usman; Sani Aliyu; O.A. Owolabi; A.B. Sallau (UMYU Journal of Microbiology Research)
Community Management of Acute Malnutrition (CMAM) is a community-based integrated approach for management of acute malnutrition. Retrospective and on the spot (present) assessment performance of community management of acute malnutrition program was carried out at Outpatient Therapeutic Programme (OTP) centers in Wagini of Batsari Local Government Area of Katsina State with the aim of assessing the performance of the programme in the locality. Assess coverage and other performance indicators of CMAM programme, biochemical and hematological parameters of children with severe acute malnutrition (SAM) and relapse rate were indices assessed using standard procedures. Point (95.66%), treatment (87.70%) and period (96.26%) were significantly (p<0.05) higher than the 50% (rural coverage) and 70% urban coverage stipulated by the SPHERE standard and there was no significant difference (p>0.05) in the coverage data between the retrospective study and present study. The performance indices: cure rate (93.19%), death rate (5.65%), default rate (13.27%) and non-recovery rate (3%) are classified as good performance when compared with SPHERE standard. There were also no significant differences (p> 0.05) among the performance indices in the retrospective and present study. There was also a notable steady improvement in the growth performance and recovery indices (Mid Upper Arm Circumference Weight for height and Oedema) among the SAM children admitted to the OTP Centers for the 8 week period. Similarly, significant (p<0.05) improvements were recorded in the biochemical and haematological indices determined (Packed cell volume, Haemoglobin concentrations, Serum albumin and glucose concentrations) in both study groups at the point of discharge and the average relapse rates determined for SAM children at wagini OTP center was 10%. From these results, the CMAM programme in Wagini, Batsari LGA of Katsina State is running well in alleviating the SAM burden in the coverage area. There is the need to work with other partners especially World Food Program (WFP) Action against hunger (AAH) for the harmonization and integration of Supplementary Feeding Program (SFP).